SITER BARUNG GAYA SURAKARTA TEKNIK DAN PENERAPANNYA - Sigit Astono (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
Siter Barung is one of the instruments (ricikan) found in Javanese Gamelan. Siter Barung is increasingly being marginalized by Siter Successor due to the increasing popularity of the Campursari genre and its accompaniments. This is solely due to the choice of recording production, which is more concerned with the variation of the high (small) sound contained in the Siter Penerus ricikan. On the other hand, the sound produced by Siter Barung tends to be softer and lower pitched (more significant) than Siter Successor. If faced with Siter barung, then, of course, the choice fell on Siter Successor because his voice was louder, higher, and more prominent. Inside the keyboard, musical instruments can be played similarly to the sound of the Keroncong musical instrument Cak. This phenomenon causes the younger generation to lack attention and enthusiasm to learn Siter Barung because they are not appreciated in the industrial world or performances. To anticipate the extinction of Siter Barung's ricikan, the author tries to convey the technique, twist, and its application in a gending, so that Siter Barung gets more attention from the next generation.